Ruthenium Complexes as Antitumor Agents – Current Status and Perspective - Grgurić-Šipka, Sanja (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
The unique characteristics of metal-based compounds make them attractive as therapeutic and imaging agents. In the treatment of cancer, metal complexes have occupied an important place, helping to cure or prolong millions of lives. The most famous complex, cisplatin (cis-diamminedichloridoplatinum(II)), used alone or in combination therapy, is one of the most successful therapeutic metallodrugs discovered so far. Its limitations, such as drug resistance, limited spectrum of activity, and worsening side effects, have initiated efforts to critically consider other metal-based complexes with cytotoxic properties. Anticancer Ru complexes gained significant interest after two iconic Ru(III) complexes – NAMI-A ((ImH)[trans-RuCl4(dmso-S)(Im)], Im = imidazole) and KP1339 (later renamed as IT-139 and BOLD-100, Na[trans-RuCl4(Ind)2], Ind = indazole) – entered their first human clinical trials at the beginning of the 21st century. The successful completion of phase I and entry into phase II clinical trials of the phototherapeutic TLD1433 has further enhanced the role of Ru as a metal of choice for the design of new anticancer agents. Besides, the ruthenium(II)-arene motif, modifiable through mono- or bidentate ligands, and halide coordination also provide complexes with excellent antiproliferative activity. To conclude, ruthenium compounds hold significant promise due to their diverse structures, mechanism of action, and potential to overcome limitations associated with traditional anticancer agents.